2014 37th International Convention on Information and Communication Technology, Electronics and Microelectronics (MIPRO) 2014
DOI: 10.1109/mipro.2014.6859759
|View full text |Cite
|
Sign up to set email alerts
|

Retaining expressions on de-identified faces

Abstract: Abstract-The extensive use of video surveillance along with advances in face recognition has ignited concerns about the privacy of the people identifiable in recorded documents. Prior research into face de-identification algorithms has successfully proposed k-anonymity methods that guarantee to thwart face recognition software. However, there has been little investigation into the preservation of the data utility such as gender and expression in the original images. To address this challenge, a new algorithm b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…The proposed face de-identification methods form clusters based on Euclidean distance in the AAM feature space. Experimental results from our previous work [6], [9] showed that the reidentification risk is near zero if the attacker uses AAM face representation and matches faces based on Euclidean distance as well. To fully evaluate the privacy protection performance of our proposed methods, further evaluation experiments have been conducted which used various face representation models and distance measures, including Eigenface (PCA) [10], Local Binary Patterns (LBPs) [11], Histogram of Oriented Gradient (HOG) [12] and Local Phase Quantization (LPQ) features [13].…”
Section: Re-identification Risk Of the De-identified Facesmentioning
confidence: 96%
“…The proposed face de-identification methods form clusters based on Euclidean distance in the AAM feature space. Experimental results from our previous work [6], [9] showed that the reidentification risk is near zero if the attacker uses AAM face representation and matches faces based on Euclidean distance as well. To fully evaluate the privacy protection performance of our proposed methods, further evaluation experiments have been conducted which used various face representation models and distance measures, including Eigenface (PCA) [10], Local Binary Patterns (LBPs) [11], Histogram of Oriented Gradient (HOG) [12] and Local Phase Quantization (LPQ) features [13].…”
Section: Re-identification Risk Of the De-identified Facesmentioning
confidence: 96%
“…For both algorithms, there are two main problems: they operate on a closed set I, and the determination of the proper privacy constraint k. In order to produce de-identified images of much better quality and preserve the data utility, the Model-based k-Same algorithms [70] are proposed -one of which is based on Active Appearance Models (AAMs) [72] and another based on the model that is the result of mixtures of identity and non-identity components obtained by factorizing the input images. Modifications to the k-Same Select algorithm, in order to improve the naturalness of the deidentified face images (by retaining face expression) and privacy protection, are proposed in [73,74].…”
Section: Face De-identification In Still Imagesmentioning
confidence: 99%
“…Option two performs k-Same-furthest face de-identification without consideration of data utility preservation and then restores the lost utility on the de-identified face generated by kSame-furthest. The second option has been tested by the work presented in [12].…”
Section: A a Better K-same Solutionmentioning
confidence: 99%